The Effect of Transactional Dialogue in Teaching Speaking Modalities - Amir, Muhammad Natsir; Adijaya, Nuryansyah (English Department, Faculty of Education, Universitas Muhammadiyah Jakarta, 2023)
The purpose of this study was to determine whether using transactional dialogue in teaching speaking modalities experimentally improved students speaking skills. This study was conducted at SMP YPI Bintaro, the sample participants were thirty-five seventh grade students. In choosing the sample, the researchers used simple random sampling technique. This study used a quantitative method with a pre-experimental design of one group pre and post-test. The instrument used in this study was spoken test used in transactional dialogue. According to the findings of this study, the students' mean score was 64.91, while their post-test score was 68.02. The statistical hypothesis revealed that the level of significance is greater than 0.000<0.005. This means that Ho (Negative Hypothesis) was rejected and H1 was accepted. Thus, transactional dialogue in teaching speaking modalities improved students' speaking skills.